Effect of a Silver Nanoparticles Solution on Staphylococcus aureus and Candida spp. - Wady, Amanda Fucci [UNESP]; Machado, Ana Lucia [UNESP]; Foggi, Camila Cristina [UNESP]; Zamperini, Camila Andrade [UNESP]; Zucolotto, Valtencir; Moffa, Eduardo Buozi [UNESP]; Vergani, Carlos Eduardo [UNESP] (Hindawi Publishing Corporation, 2014)
An AgNPs solution was synthesized by chemical reduction, characterized, and tested against Candida glabrata, Candida tropicalis, Staphylococcus aureus, and methicillin-resistant Staphylococcus aureus (MRSA). Minimum inhibitory (MICs) and minimum fungicidal/bactericidal concentrations (MFC/MBC) were determined on planktonic cells. Also, total biofilm mass was determined by crystal violet (CV) staining and morphological changes by scanning electron microscope (SEM). MICs for C. glabrata, C. tropicalis, S. aureus, and MRSA were 15.63, 3.91, 1.95, and 1.95 mu g/mL, respectively. MFC for C. glabrata was 62.5 mu g/mL and for C. tropicalis 15.63 mu g/mL The same MBC (3.91 mu g/mL) was observed for S. aureus and MRSA. CV assay showed that the AgNPs (1000 mu g/mL) promoted reductions in biofilm mass of similar to 60% for C. glabrata and similar to 35% for C. tropicalis. A reduction of similar to 20% in C. tropicalis biomass was also observed at the concentration of 3.91 mu g/mL. No significant effect on total biomass was found for S. aureus and MRSA. SEM images revealed that C. glabrata and C. tropicalis biofilm cells, exposed to the AgNPs (1000 mu g/mL), had an irregular and shriveled appearance. AgNPs solution exhibited considerable antimicrobial activity against important fungal and bacterial pathogens, associated with several oral and systemic diseases, and has potential as an antimicrobial agent.